Overestimating the Self, Outranking the Group: An Experimental Study of Overconfidence Biases in Young Decision-Makers - Guner Gultekin, Duygu; Akinci, Funda Nur (MDPI, 2025)
Cognitive biases have been proved to have a systematic influence on decision-making at both individual and social levels. This study investigated two forms of overconfidence-specifically, overestimation and overplacement-among young individuals participating in a social prediction task using an experimental design. The experimental study was conducted with 414 undergraduate students during an in-class written exam. Participants were drawn from different courses taught by the same instructor and varied in terms of their level of prior interaction with the instructor (having attended one, two, or three semesters). Participants predicted the instructor's favourite songs and subsequently evaluated the accuracy of their own predictions and those of their classmates. This experimental design allowed the researchers to look at both how accurately participants judged themselves and how they compared themselves to their peers. The analysis primarily focused on discrepancies between self-evaluated and actual performance. Results revealed a consistent pattern of overestimation and overplacement. Participants rated themselves as more successful than they actually were and positioned themselves above the average of their peer group. Moreover, the lack of direct feedback and limited contextual cues in the guessing task created a psychological ambiguity, which may have contributed to an unjustified sense of certainty among the participants. These findings offer empirical insight into the functioning of cognitive biases and contribute to a nuanced understanding of overconfidence in young decision-makers.
Keywords: overconfidence bias; overplacement; overestimation; cognitive biases; GENDER-DIFFERENCES; CONFIDENCE; PEOPLE; PERCEPTIONS; PREFERENCES; UNCERTAINTY; COMPETITION; UNAWARE; SKILLS; WOMEN; Psychology